Exoproteome Analysis of Human Pathogenic Dermatophyte Species and Identification of Immunoreactive Proteins. Issue 6 (18th July 2018) - Eymann, Christine; Wachlin, Gerhild; Albrecht, Dirk; Tiede, Stephan; Krummrei, Ulrike; Jünger, Michael; Hecker, Michael; Daeschlein, Georg
Abstract: Purpose: Increasing incidence of onychomycosis and tinea pedis in humans of industrialized countries together with deep tissue infections are a therapeutic challenge in clinical mycology. For a better understanding of the pathology and immunology of infection, the authors analyze the exoproteomes of three reference strains of the most common clinical dermatophyte species ( Trichophyton rubrum, Trichophyton interdigitale, Arthroderma benhamiae ) and of Trichophyton strains isolated from affected patients. Experimental design: Extracellular proteins of those in vitro grown strains are separated via 2D High Performance Electrophoresis and identified by mass spectrometry to find proteins with provoked host immune reactivity. Results: More than 80 secreted proteins including virulence factors such as peptidases and other hydrolases are identified. By Western blotting with respective patient sera, up to 31 proteins with significant antigen–antibody reactions are detected in comparison with control sera, for example, peptidases as well as several oxidoreductases. One protein, beta‐glucosidase F2SZI9 seems to be a commonly processed antigen in all Trichophyton infections. Conclusions and clinical relevance: These first global exoproteome data of three dermatophyte species can be a stepping stone on the way to further study the molecular mechanisms of Trichophyton pathogenicity‐associated traits. Possible candidates for potential new diagnostic methods or vaccination have to be validated in further investigations.